EFFECTS OF RURAL-URBAN MIGRATION ON FARMING POPULATION IN IJUMU LOCAL GOVERNMENT AREA, KOGI STATE, NIGERIA - Olowogbayi, J.A.; Ishola, S.O.; Ogunsina, I. B. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study investigated the effects of rural–urban migration on farming population in Ijumu Local Government Area (LGA), Kogi State, Nigeria. The persistent rise in rural out‑migration has negatively affected labour availability for agricultural production, consequently threatening rural livelihoods and food security. The study analyzed the perceived causes of out‑migration, assessed its implications on agricultural performance, and identified strategies for reducing rural–urban youth migration. A descriptive survey involving fifty (50) respondents selected through simple random sampling was employed. Findings revealed that majority(50%) of the respondents relocate to urban centres due to unemployment and family reunification (66%) as major factors for out‑migration. Findings indicate that, decline farm operations highly (68%) affected agricultural performance as a result of reduced hired labour, lowers productivity, and reduces farm incomes. Notable strategy to alleviate out-migration is advocacy programme such as youth empowerment which captured about (62%) of the enlisted strategies. The study concludes that migration significantly undermines agricultural output and rural socio‑economic stability. Recommendations include provision of social amenities, youth empowerment, microcredit schemes, agricultural modernization, and establishment of rural agro‑allied industries to retain rural labour and improve agricultural productivity.